STUDY ON ABSORPTION OF OZONE IN WATER USING PERFORATED SIEVE TRAY COLUMN (Journal of Engineering, 2009)
The aim of this work is concerned with detailed study of transfer of ozone into water.. Since ozone cannot be stored or conveniently purchased by the gram, pound, gallon or ton, it must be produced on site as needed, (where needed and when needed). The process will carried out with two important assumptions; first that ozone is the only active species that physically dissolves in water. And second that there is no chemical reaction .the process carried out in a perforated sieve tray column with 1 m long and 33 cm diameter. The effects of process variables such as (Water flow rate, pH and air flow rate which is refer to the concentration of free ozone in the gas phase in the absorption column). The result show that the absorption rate increases with increasing the water flow rate and decreasing the air flow rate in a pH range (7-8).